Algebraic L2 Decay for Weak Solutions of the Nonlinear Heat Equations in Whole Space R3 - Yuexing Yang (Abstract and Applied Analysis)
We obtained the algebraic L2 time decay rate for weak solutions of the nonlinear heat equations with the nonlinear term ∇u2u in whole space R3. The methods are based on energy methods and Fourier analysis technique.